THE RESULTS OF THE SELECTION OF F1 HYBRIDS OF TOMATO INTENDED FOR THE MANUFACTURE OF CANNED FOOD "UNREFINED TOMATOES IN TOMATO JUICE" - T. P. Blinova; I. V. Uzun (Овощи России, 2019)
The technique of creation and the characteristic  of two draft lines of a tomato with functional male sterility (ps-2) are given. The results of the five-year  (2014-2018) test of two medium early determinant  F1  hybrids for open ground (F1   Orlik and F1 Ogonjok), based on draft sterile line 1324, are presented. New hybrids in  total yield and yield of standard fruits are not inferior to the Dutch hybrids F1   Yaqui («Seminis»)  and F1   Asterix («Syngenta»)  zoned in Transnistria and Moldova. The fruits of the new hybrids are plum-shaped (index 1,3 units), medium size (weight 50-70 g), bright red, with a shiny surface without a green spot. Сhemical composition and the physico-mechanical properties of fresh fruit meet the requirements. The content of solids in the fruit-more than 5%, total sugars - more than 3%, acidity is medium, sugar-acid index-about 7 unit. The strength of the fruit is high: the crushing force is more than 7 kg, the specific resistance to crushing is more than 120 and 140 g / g of mass, the force to puncture the skin is more than 260 and 280 g / mm2 .